Influência do cimento endodôntico na adesão do pino de fibra de vidro à dentina radicular - Menezes, Murilo de Sousa (2006)
The aim of this study was to test the hypothesis that the endodontic cement composition and the period taken between root obturation and glass fiber post cementation may interfere with bond strength on root dentin. Sixty roots of bovine incisors were instrumented and randomly assigned to 5 groups (N=12): 1, (CI), without obturation, control; 2, (SI) obturation calcium hydroxide based cement (Sealer 26) and immediate post fixation; 3, (S7) obturation with calcium hydroxide based cement and post fixation after 7 days; 4, (EI) obturation zinc oxide-eugenol based cement (Endofill) and immediate post fixation, and 5, obturation with zinc oxide-eugenol based cement and post fixation after 7 days. Glass fiber posts were cemented with a three step adhesive system (Scotchbond Multi-Purpose) and dual resinous cement (Rely- X ARC). In each group, ten roots were transversally sectioned resulting in two 1mm-thick discs on each dental third, cervical (TC), medium (TM) and apical (TA), which were submitted to the micropush-out test with a crosshead speed of 0.5mm/minute. The remaining two roots were prepared for scanning electron microscope observation. Adhesive bond strength data in MPa were submitted to analysis of variance (ANOVA) following Tukey and Dunnett tests (p<0.05): CITC: 6.8±1.5; TM: 5.4±1.9; TA: 4.4± 1.8; SI- TC: 5.2±1.6; TM: 5.0±2.0; TA: 4.1±2.2; S7- TC: 6.9±2.0; TM: 5.4±1.8; TA: 4.5±1.6; EI-TC: 3.5±0.8; TM: 2.2± 0.5; TA: 1.4±0.7; E7- TC: 6.6±1.7; TM: 4.4±1.4; TA: 2.4±0.6. Obturation with a zinc oxide-eugenol cement negatively influenced adhesion to root dentin in all its extension when post was immediately cemented, and just in the apical third was post when cemented after 7 days. The adhesive bond strength was increasingly lower in the direction crow-root for all groups.